2014
DOI: 10.1016/j.aquaculture.2013.12.032
|View full text |Cite
|
Sign up to set email alerts
|

The development of the gut microbiota in rainbow trout (Oncorhynchus mykiss) is affected by first feeding and diet type

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Archived at http://orgprints.org/24967 AbstractAn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
215
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(250 citation statements)
references
References 48 publications
28
215
6
1
Order By: Relevance
“…Further statistical analysis of the beta diversity in this study using PERMANOVA showed that multiple shifts in the gut microbial composition occurred across fish age, while ANOSIM supported these results with the detection of distinguishable separation between specific age groups (Table 2B). Ontogenetic and temporal changes in microbial beta diversity have been detected in other aquaculture fish species as well, such as rainbow trout [33], Atlantic cod [32], and coho salmon [31]. Similar microbiota shifts are commonly detected in other organisms too, including zebrafish [13, 30], humans [5356], rodents [57, 58], and terrestrial mono-gastric livestock, such as pigs and chickens [5960].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further statistical analysis of the beta diversity in this study using PERMANOVA showed that multiple shifts in the gut microbial composition occurred across fish age, while ANOSIM supported these results with the detection of distinguishable separation between specific age groups (Table 2B). Ontogenetic and temporal changes in microbial beta diversity have been detected in other aquaculture fish species as well, such as rainbow trout [33], Atlantic cod [32], and coho salmon [31]. Similar microbiota shifts are commonly detected in other organisms too, including zebrafish [13, 30], humans [5356], rodents [57, 58], and terrestrial mono-gastric livestock, such as pigs and chickens [5960].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies have explored the intestinal microbiota of aquaculture species from early larval stages through later developmental stages using molecular techniques. Yet, these studies have often been focused on marine species such as anadromous coho salmon Oncorhynchus kisutch [31] or marine Atlantic cod Gadus morhua [32], with only one such study evaluating the temporal development of the gut microbiota of a freshwater aquaculture species [33]. …”
Section: Introductionmentioning
confidence: 99%
“…The introduction of high-throughput sequencing technologies has increased our understanding of microbial diversity and function in complex environments, including the gastro- 2011; Desai et al 2012;Wu et al 2012;Boutin et al 2013;Carda-Diéguez et al 2013;Wu et al 2013;Ingerslev et al 2014;Zarkasi et al 2014;Falcinelli et al 2015). At present, there is a paucity of information on the intestinal microbiome of tilapia using high-throughput sequencing; to the author's knowledge, this is the first study utilising high-throughput sequencing to assess the intestinal microbial communities in this fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation samples were spun at 13,000 ϫ g for 10 min, and the DNA contained in the cell pellets was purified with a Maxwell LEV blood DNA purification kit (Promega Corporation, Madison, WI, USA) as described by Ingerslev et al (40).…”
Section: Methodsmentioning
confidence: 99%